Determinants Of Regional Financial Management Performance And The Moderation Effect Of Malaqbiq Culture In West Sulawesi Province - Yani, Muh; Mattalata, Mattalata; Ansar, Ansar; Farida, Umi; Sandra, Kurniawaty (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the determinants of village financial management performance and the moderating effect of malaqbi culture in Mamuju Regency, West Sulawesi Province. The main focus of this study is to examine the relationship between leadership, commitment, and competence of village financial managers with financial management performance, and how malaqbi culture can moderate the relationship. Malaqbi, which is a local culture that emphasizes the values ​​of honesty, responsibility, and integrity, is believed to play an important role in increasing transparency and accountability in village financial management.Specifically, this study identifies the main problems in village financial management in Mamuju Regency, which include violations, abuse of authority, and corruption that still occur. The existence of these problems indicates deficiencies in financial management caused by institutional factors, such as lack of effective leadership, low commitment, and limited competence of village financial managers. This study proposes that the application of malaqbi culture based on local moral and ethical values ​​can function as a moderation that can increase the influence of leadership, commitment, and competence on village financial management performance.Using a quantitative approach, this study will examine the direct influence of these variables and how malaqbi can strengthen or weaken these relationships. It is hoped that the findings of this study can contribute to a deeper understanding of the importance of local culture in improving the performance of village financial management, as well as offering solutions to overcome various village financial problems that still occur, including violations and corruption.